Forecasts and Reactivity - Reto Cueni; Bruno S. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2014)
Forecasters' estimates influence peoples' expectations, their decisions and thus also actual market outcomes. Such reactivity to forecasts induces externalities which harm the ex-post assessment of the forecasters' accuracy and in turn the improvement of forecasting accuracy and market outcomes. To empirically analyze the impact of reactivity on forecast accuracy, we compare the development of the forecast error in a non-reactive system, such as the market for weather forecasts, to reactive systems, such as the stock and the art market. The evidence strongly supports our proposition that in reactive systems, despite the vast increase of data and processing techniques, forecast accuracy did not improve, while forecast accuracy in non-reactive systems did.
Keywords: 330